Response of a packaging system to a transient event: Real‐time replication versus shock response spectra simulation. Issue 9 (1st May 2022) - Bonnin, Anne‐Sophie; Nolot, Jean‐Baptise; Huart, Victor; Pellot, Jérôme; Krajka, Nicolas; Odof, Serge; Erre, Damien
Abstract: Vibrations and shocks are found among mechanical phenomena undergone by packaging systems. In order to verify the behaviour of packaging systems under shocks, test protocols advocate the execution of drop tests, inclined plane tests, forklift handling courses and so on in laboratories. Nevertheless, even if these protocols are efficient, they do not replicate the wide variety of transient events occurring during transportation. That is why there is a need in developing a method capable of replicating actual transient events in a reproductive way in laboratories. This work concerns the comparison of the responses of a packaging system subjected to two different simulations of the same transient event with the aim to forward develop specifications. The definition and elaboration of shock response spectra (SRS) are reviewed in the first part of this work. Afterwards, a data acquisition enables the recording of classical transient events generated by a forklift. Then the calculation of the SRS of one of those transient events enables the generation of a time signal different from the transient event recorded. Finally, a comparison between the response of a packaging system subjected to the time transient event as it is recorded and the response to the time transient event calculated from the SRS is carried out. The first results based on the study of autocorrelation functions, intercorrelation functions, energy spectral densities (ESDs) and damage calculation conclude towards an equivalence between a real‐time replication and an SRS simulation in the case of one transient event and one packaging system. Abstract : This work concerns the comparison of the responses of a packaging system subjected to two different simulations of the same transient event with the aim to forward develop specifications. The first results based on the study of autocorrelation functions, intercorrelation functions, energy spectral densities and damage calculation conclude towards an equivalence between a real‐time replication and a shock response spectra simulation in the case of one transient event and one packaging system.